The Influence of Environmentally Friendly HRM on Environmentally Friendly OCB: The Mediating Role of Organizational Identification, Job Satisfaction, and Environmentally Friendly Culture - Kristanto Prasetyo Aji; Asri Laksmi Riani (Transpublika Publisher, 2025)
The goal of this research is to investigate how Green Human Resource Management (GHRM) impacts Green Organizational Citizenship Behavior (G-OCB), with the involvement of organizational identification, job satisfaction, and green culture. The methodology utilised for this study is a survey. The target group for this research comprises of postgraduate students from the Faculty of Economics and Business at Universitas Sebelas Maret, who are currently working in various sectors. A purposive sampling approach was employed, with a total of 140 participants. Analysis of the data was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM). The study shows that GHRM has a notable impact on organizational identification, but organizational identification has no significant impact on G-OCB. In addition, GHRM has a significant influence on job satisfaction, while job satisfaction does not significantly affect G-OCB. Moreover, GHRM has a significant effect on green culture, and green culture also has a significant impact on G-OCB. The findings suggest that organizational identification does not act as a mediator between GHRM and G-OCB, and job satisfaction does not mediate the relationship either. However, green culture is found to be a mediator in the relationship between GHRM and G-OCB.